Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Karjawan Distrik Sorong Utara - Irene Yuliana Edowai; Edward Clan; Andre Maryen (Departement of Mathematics Education, 2023)
The influence of excessive workload can create an uncomfortable working atmosphere for workers. Excessive work load can trigger the emergence of work stress more quickly. On the other hand, a lack of workload can cause losses for the organization/agency. This is because the responsibilities given by the government for the work do not match the abilities possessed by the workers, which can result in errors in financing the work of employees in the North Sorong District. Problems that occur due to the varying characteristics of the human resources they have and the mismatch between the workload and the capabilities of the human resources can result in the work being given to be of poor quality. Based on this problem, the researcher defines and uses the title